2021
DOI: 10.1136/bmjopen-2021-050189
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of COVID-19-related knowledge and preventive behaviours among students in reopened secondary schools: cross-sectional study

Abstract: PurposeIn Ethiopia, more than 26 million students have been out of the classroom for nearly 9 months. On 18 September, the Ethiopian Minister of Health advised the Parliament the possibility of reopening schools provided certain conditions were met. Schools are currently reopening in the country for the first time since March 2020.ObjectiveThis study assessed the knowledge and preventive health behaviours toward COVID-19 and associated factors among secondary school students.Design, setting, participants and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 20 publications
3
23
2
Order By: Relevance
“…This may be due to a difference in source population and difference in sample size as such factors may influence findings. Whereas, the result of this study is higher as compared with a study conducted at Gondar city secondary school students [18], on Bangladesh residents, a study conducted among undergraduate students at Debre Birhan University, and a study conducted on quarantined individuals in Tigray which showed that 23.5%, 48.3%, 73.8%, and 42.9% of the participants had accurate knowledge towards COVID-19 respectively [19][20][21]. It is also higher as compared with a study done on Jimma University medical center visitors which showed that 41.3% of the participants had a high knowledge level towards COVID-19 [22].…”
Section: Plos Onecontrasting
confidence: 85%
“…This may be due to a difference in source population and difference in sample size as such factors may influence findings. Whereas, the result of this study is higher as compared with a study conducted at Gondar city secondary school students [18], on Bangladesh residents, a study conducted among undergraduate students at Debre Birhan University, and a study conducted on quarantined individuals in Tigray which showed that 23.5%, 48.3%, 73.8%, and 42.9% of the participants had accurate knowledge towards COVID-19 respectively [19][20][21]. It is also higher as compared with a study done on Jimma University medical center visitors which showed that 41.3% of the participants had a high knowledge level towards COVID-19 [22].…”
Section: Plos Onecontrasting
confidence: 85%
“…The articles included are from the following authors: Abebe et al [26] ; Acheampong et al [28] ; Adebisi et al [17]; Adeniyi et al [30] ; Aemro et al [31] ; Agyekum et al [32]; Angelo et al [34] ; Amuzie et al [33] ; Bongomin et al [18] ; Dinga et al [27] ; Ditekema et al [19] ; Echoru et al [20] ; El Kefi et al [35] ; El Sokkary et al [39] ; Elhadi et al [21] ; Fares et al [22] ; Handebo et al [23]; Kanyike et al [29]; Mose et al [24] ; Oduwole et al ; Omar et al [37] ; Oyekale et al [38] ; Saied et al [25]. Individual characteristics of the included studies are presented in tables 1, 2, and 3.…”
Section: Resultsmentioning
confidence: 99%
“…The reported finding on correct responses to most of the knowledge questions was expected because the survey was conducted at the very peak stage of the pandemic worldwide (early April 2020). A recent study conducted in northern Ethiopia (Gondar) based on 370 secondary school students reported that only a quarter (23.5 percent, 95 percent confidence interval [CI] = [19.5, 28.1]) of the participants had good knowledge of COVID-19 (Handebo et al 2021). Comparable studies conducted in China and other South Asian countries at the peak of the pandemic report a similarly higher knowledge level among the public (G. Huynh et al 2020;Zhong et al 2020).…”
Section: Knowledge Attitude and Risk Perception Of Covid-19mentioning
confidence: 99%
“…For instance, some of them (e.g., Jemal et al 2020; Kebede et al 2020; Tadesse et al 2020) have drawn samples from health facilities and focused on health professionals. Other studies (e.g., Addis et al 2020; Feyisa 2021; Handebo et al 2021) are population-based but had a small sample size from a particular region or town. Although such assessments are vital and provide useful insights into outbreaks of a pandemic such as COVID-19, these studies may be less useful for policy making.…”
Section: Introductionmentioning
confidence: 99%